The Darkest Hue (Instagram, 2021)
"Jeymes Samuel isn’t much more imaginative than white Hollywood writers and directors. He can’t imagine Stagecoach Mary looking how she did- a beautiful fat, tall, dark-skinned Black woman- and being desired. His casting choices may reflect his *gendered* colorist biases. He hand-picked dark-skinned, monoracial Black actors to play the big, strong, and tough cowboys, despite most of the real-life male characters being fair-complected and mixed-raced. The first person he chose to be Stagecoach Mary was Erykah Badu, a light-brown skinned, thin, and green-eyed Black woman in his 2013 short film They Die by Dawn. He recently chose Zazie Beatz, a light-skinned biracial actress, to play Stagecoach Mary. This infographic essay explores what could have informed these decisions. Light skinned and biracial actresses also have a responsibility to turn down these roles (see slide 9). Don't forget to support me (last slide) if you're able to! #colorism #stagecoachmary #zaziebeetz #thehardertheyfall #jeymesamuel #explorepage #explorepage"
Keywords: 2000 à aujourd'hui; approches et analyses; colorisme; corps; cours; fem3300; intersectionnalité; militance; premier cycle; périodes historiques; racisme; ressource en ligne; sexisme; systèmes d'oppressions; thématiques; violences